A Reconfigurable Access Scheme for Massive-MIMO MTC Networks - Atoosa Dalili Shoaei; Duc Tuong Nguyen; Tho Le-Ngoc (IEEE Access)
This paper presents an efficient reconfigurable access scheme for massive machine-type communication networks, where to provide massive connectivity, the base station is equipped with a large-scale antenna array. In particular, to maximize the expected throughput of the network, the scheme uses a frame divided into two segments: grant-based and grant-free that are more efficient for devices with high and low expected throughput, respectively. At the beginning of each frame, the base station decides how to partition the two segments, the resource allocation in the grant-based segment and the access probabilities in the grant-free segment to maximize the expected throughput based on the device traffic profiles. The corresponding optimization problem is formulated, and a sub-optimal solution algorithm with low computational complexity is proposed. The performance of the proposed access scheme is evaluated under different conditions to demonstrate its advantages in terms of achieved throughput and average packet delay.